Re-Examining the Concept of Ta’dib in the Government of Umar bin Abdul Aziz as a Revolutionary Leader - Handayani, Ega Putri; Ulfah, Maulidani; Arief, Asmawaty; Khadijah, Khadijah (YASIN, 2024)
Umar bin Abdul Aziz was the son of the best official of the Umayyah Dynasty, who was known to be generous and diligent in studying the science of hadith. His mother was Umm bin Abdul Aziz, a descendant of Umar bin Khattab, so it is not surprising that he inherited many of Umar's noble qualities. This study reveals the application of ta’dib in the government of Umar bin Abdul Aziz during the Umayyad Dynasty. The researcher used library research by taking various literature from books, scientific journals, and different related documents. The results of the study show that Umar bin Abdul Aziz is known as one of the caliphs whose government was recorded as the golden age of Islam due to his success in making his people prosperous so that no one needed zakat. The nature of tarbiyah, ta'lim, and ta’dib in the concept of Islamic education carried out by both of his parents made Umar bin Abdul Aziz successful in leading the Umayyah Dynasty. Even though it was not very long (717-720 AD), his policies were imposed and loved by his people, so the policies implemented by Umar bin Abdul Aziz can be used as a reference and guideline in a modern government today, especially in eradicating corruption in a country.